Consumer Behavioral Drivers: The Effects of e-WOM, Brand Attitude, and Brand Image on Skintific Purchase Intention - Nafis, Fitya Hilyatin; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to examine the influence of electronic word-of-mouth (e-WOM), brand attitude, and brand image on the purchase intentions for Skintific products among skincare consumers in Malang City. This quantitative explanatory research elucidates the causal relationships between the variables through hypothesis testing. A total of 183 respondents were selected, with the sample size calculated using Cochran's formula. The data was collected through a Likert-scale questionnaire that had undergone validity and reliability testing. The collected data was tested using classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity tests, followed by multiple regression analysis. Furthermore, model accuracy (F-test), coefficient of determination (R²), and partial regression coefficient (t-test) were conducted for hypothesis testing. This study finds that electronic word-of-mouth negatively influences the purchase intention for Skintific skincare products in Malang City, that brand attitude and brand image positively influence the purchase intention, and that electronic word-of-mouth, brand attitude, and brand image simultaneously have a positive influence on purchase intention.